Effectiveness and safety of bimekizumab for the treatment of plaque psoriasis: a real-life multicenter study—IL PSO (Italian landscape psoriasis) - Gargiulo, Luigi; Narcisi, Alessandra; Ibba, Luciano; Balato, Anna; Bianchi, Luca; Brianti, Pina; Buononato, Dario; Burlando, Martina; Caldarola, Giacomo; Campanati, Anna; Campione, Elena; Carrera, Carlo G.; et al. (Frontiers in Medicine, 2023)
Bimekizumab is a monoclonal antibody that targets Interleukin-17 A and F, approved for the treatment of moderate-to-severe plaque psoriasis. While bimekizumab has been evaluated in several phase-III clinical trials, real-world evidence is still very limited.This multicenter retrospective study included patients affected by plaque psoriasis treated with bimekizumab from May 1, 2022 to April 30, 2023, at 19 Italian Referral Hospitals. Patients affected by moderate-to-severe plaque psoriasis eligible for systemic treatments were included. The effectiveness of bimekizumab was evaluated in terms of reduction in Psoriasis Area and Severity Index (PASI) compared with baseline at weeks 4 and 16. The main outcomes were the percentages of patients achieving an improvement of at least 75% (PASI75), 90% (PASI90) and 100% (PASI100) in PASI score.The study included 237 patients who received at least one injection of bimekizumab. One hundred and seventy-one patients and 114 reached four and 16 weeks of follow-up, respectively. Complete skin clearance was achieved by 43.3% and 75.4% of patients at weeks 4 and 16, respectively. At week 16, 86.8% of patients reported no impact on their quality of life. At week 16, there were no significant differences between bio-naïve and bio-experienced patients in terms of PASI75, PASI90 and PASI100. The most commonly reported adverse events (AEs) were oral candidiasis (10.1%). No severe AEs or AEs leading to discontinuation were observed throughout the study.Our experience supports the effectiveness and tolerability of bimekizumab in a realworld setting with similar results compared with phase-III clinical trials.